Development and Standardization of Persian Language Developmental Battery - Reza Nilipour; Zahra Sadat Qoreishi; Hourieh Ahadi; Abbas Pourshahbaz (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective In the absence of an age normed developmental battery for Persian, the major objectives of this research are to develop a reliable and valid clinical linguistic battery to collect normative data from 3 to 7-year-old healthy Persian speaking children. The battery can also be used to measure severity of language impairments in 3 to 7-year-old Persian speaking children as compared with their aged matched peers. Materials & Methods Development of this battery is considered as a descriptive tool in which reliability and validity of the normative data were developed in 3 stages. The first version with 9 different sub-tests, 180 items and two descriptive pictures was developed after cultural and linguistic adaptations for the Persian language for different linguistic levels of phonology, morphology, syntax and pragmatics. The first draft was performed using 200 3 to 8-year-old healthy children in Tehran to measure the sensitivity of different tasks of the test for different age groups. This draft was not sensitive for 8-year-old children. The CVR of the first draft of the battery was checked by 3 Persian speaking clinical linguistic experts and 3 expert speech therapists and also was introduced to 20 SLP experts in a clinical linguistic workshop. In the second stage, based on the results and suggestions, necessary corrections were made in the test structure and items. Also, plural morpheme task of the previous version which was not sensitive enough, was removed and a new semantic task (word definition) as a sensitive semantic task used in other developmental language batteries was added to the battery. The results showed that the diagnostic sensitivity of the test for the 8-year-old age group is not satisfactory. The final version of the battery consisted of 9 subtests with 105 items and two descriptive pictures were used to collect normative data from 200 children. To evaluate reliability and validity of the final version, the opinions of 8 speech therapists and linguists were used.and to evaluate the construct validity, the correlation matrix and confirmatory factor analysis and for its validity Cronbach's alpha were used. The final version of the battery was sent to expert speech therapists in 5 selected target group provinces (Tehran, Mazandaran, Fars, Esfahan and Khorasan) to collect normative data from 1200 3 to 7-year-old typically developement children in available kindergartens and schools. Finally, the collected data for task items and connected speech measures were processed and analyzed using SPSS software, version 20. Results The content validity was 0.78 and test reliability was 0.76. In addition to confirm the construct validity and diagnostic validity of the test, the correlation between the sub-tests and the overall test scores were also significant at the level of 0.01 (with a correlation of 0.20 to 0.83). The norm for each age group was six months and one year and was calculated as a standard score and reported in the tables. Conclusion Finally, the results of the normative data of this battery are proved to be clinically normative as an indication of the level of linguistic development for each age group and also determine the severity of their language impairment. The battery can also be used to measure the efficacy of rehabilitation in 3 to 7-year old Persian speaking children.